Halotolerant Fungi in Salted and Dried Fish at Lower Visakhapatnam Coast - R., Chakrabarti; P.R.G., Varma (Fishery Technology, 2025)
Aspergillus flavus, Aspergillus niger, Penicillium sp. and Mucor were the common halotolerant fungi present in salted and dried fish at lower Visakhapatnam coast. The time required for growth of fungal colony to visible range was different in different types of salted and dried fish and it also varied with the season. Visible fungal colonies appeared rapidly in rainy season and it took longest time in winter season. Seasonal variations in the levels of moisture, sodium chloride, total volatile bases and water activity were also observed.